Urgensi Asbabun Nuzul bagi Seorang Mufassir dalam Menafsirkan Ayat Al-Qur'an - Al Amin, Ahmad Yasir; Baidan, Nashruddin (ANWARUL, 2024)
The Qur'an is the Word of Allah, revealed to Prophet Muhammad (peace be upon him) through the intermediary of the angel Gabriel in a continuous and well-documented manner. It serves as a miracle and a guide for humanity. The Qur'an was revealed to Prophet Muhammad (peace be upon him) at specific times and during particular events. Therefore, understanding the reasons for the revelation of the Qur'an is a fundamental basis for a commentator (mufassir) to interpret its verses and implications in the establishment of Sharia law. By comprehending the interpretation correctly and understanding the establishment of Sharia law, we can extract wisdom from it and find motivation to fulfill what is contained within the Qur'an.